تصور مقترح للجانب التطبيقي لنظريات الرضا الوظيفي للأستاذ الجامعي في الجامعات العراقية (Journal of the College of Basic Education, 2025)
The research aimed to shed light on how to apply the theories that address job satisfaction for university professors in Iraqi universities and the possibility of achieving them. The research dealt with international theories that call for job satisfaction for university professors in general and broadly. Then the researcher presented some Arab and foreign studies that speak On this vital topic, the researcher tried to reconcile the main opinions and proposals for job satisfaction and concluded from them some proposals that suit the Iraqi environment and at the same time satisfy the aspirations of university professors in Iraqi universities.